Extremal Graphs for a Bound on the Roman Domination Number - Bouchou Ahmed; Blidia Mostafa; Chellali Mustapha (Discussiones Mathematicae Graph Theory, 2020)
A Roman dominating function on a graph G = (V, E) is a function f:V (G) → {0, 1, 2} such that every vertex u for which f(u) = 0 is adjacent to at least one vertex v with f(v) = 2. The weight of a Roman dominating function is the value w(f) = Σu∈V(G)f(u). The minimum weight of a Roman dominating function on a graph G is called the Roman domination number of G, denoted by γR(G). In 2009, Chambers, Kinnersley, Prince and West proved that for any graph G with n vertices and maximum degree Δ, γR(G) ≤ n + 1 − Δ. In this paper, we give a characterization of graphs attaining the previous bound including trees, regular and semiregular graphs. Moreover, we prove that the problem of deciding whether γR(G) = n + 1 − Δ is co-𝒩 𝒫-complete. Finally, we provide a characterization of extremal graphs of a Nordhaus–Gaddum bound for γR(G) + γR (Ḡ), where Ḡ is the complement graph of G.